2011
DOI: 10.1890/10-1386.1
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐reproductive survival in a tropical bird and its implications for avian life histories

Abstract: The factors that affect survival until reproduction are essential to understanding the organization of life histories within and among species. Theory predicts, for example, that survival until reproduction influences the optimum level of reproductive investment by parents, which might partly explain prolonged parental care in species with high first-year survival. Tests and refinements of life-history theory have been hampered, however, by a lack of field-based estimates of pre-reproductive survival, especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 40 publications
4
66
0
Order By: Relevance
“…If this extended parental care results in increased survival of juvenile birds, it is conceivable that a latitudinal change in juvenile survival might offset the latitudinal change in clutch size. Indeed, when Tarwater et al (2011) estimated the survival of juveniles from fledgling to 1 yr of age in a Central American population of Black-crowned Antshrikes (Thamnophilus atrinucha), they obtained a value of nearly 50%, which is above the range of prereproductive survival for 7 species of North American birds that they used for comparison. Tarwater et al (2011) suggested that a relatively high pre-reproductive survival among tropical birds might resolve the apparent contradiction between the latitudinal trend in clutch size and the overlap of adult survival estimates across latitudes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…If this extended parental care results in increased survival of juvenile birds, it is conceivable that a latitudinal change in juvenile survival might offset the latitudinal change in clutch size. Indeed, when Tarwater et al (2011) estimated the survival of juveniles from fledgling to 1 yr of age in a Central American population of Black-crowned Antshrikes (Thamnophilus atrinucha), they obtained a value of nearly 50%, which is above the range of prereproductive survival for 7 species of North American birds that they used for comparison. Tarwater et al (2011) suggested that a relatively high pre-reproductive survival among tropical birds might resolve the apparent contradiction between the latitudinal trend in clutch size and the overlap of adult survival estimates across latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, when Tarwater et al (2011) estimated the survival of juveniles from fledgling to 1 yr of age in a Central American population of Black-crowned Antshrikes (Thamnophilus atrinucha), they obtained a value of nearly 50%, which is above the range of prereproductive survival for 7 species of North American birds that they used for comparison. Tarwater et al (2011) suggested that a relatively high pre-reproductive survival among tropical birds might resolve the apparent contradiction between the latitudinal trend in clutch size and the overlap of adult survival estimates across latitudes. Their reliance on a small number of species is a reflection of data availability; tropical studies of variation in survival as a function of age are rare and usually focus on single species (e.g., Anders et al 1997, Tarwater et al 2011, whereas information on clutch size can be mapped for thousands of species around the world (Jetz et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most if not all studies show a dip in daily survival during the first few days after fledging (Sullivan 1989, Anders et al 1997Sim et al 2013;Kershner et al 2004;Tarwater et al 2011 ;Yackel Adams et al 2006;NaefDaenzer et al 2001;Dybala et al 2013). In addition, some studies show a second dip after the nestlings have become independent (Sullivan 1989;Anders et al 1997;Sim et al 2013) although others do not (Kershner et al 2004;Tarwater et al 2011;Yackel Adams et al 2006;Naef-Daenzer et al 2001).…”
Section: Stage-dependent Survivalmentioning
confidence: 99%
“…In addition, some studies show a second dip after the nestlings have become independent (Sullivan 1989;Anders et al 1997;Sim et al 2013) although others do not (Kershner et al 2004;Tarwater et al 2011;Yackel Adams et al 2006;Naef-Daenzer et al 2001). We divided survival into two periods (B4 and [4 weeks after fledging) and found some support for differential survival between them.…”
Section: Stage-dependent Survivalmentioning
confidence: 99%